An evaluation framework for research platforms to advance cochlear implant/hearing aid technology: A case study with CCi-MOBILE - Shekar, Ram C. M. C. (J Acoust Soc Am, 2021)
Cochlear implants (CIs) and hearing aids (HAs) are advanced assistive hearing devices that perform sound processing to achieve acoustic to acoustic/electrical stimulation, thus enabling the prospects for hearing restoration and rehabilitation. Since commercial CIs/HAs are typically constrained by manufacturer design/production constraints, it is necessary for researchers to use research platforms (RPs) to advance algorithms and conduct investigational studies with CI/HA subjects. While previous CI/HA research platforms exist, no study has explored establishing a formal evaluation protocol for the operational safety and reliability of RPs. This study proposes a two-phase analysis and evaluation paradigm for RPs. In the acoustic phase 1 step, a signal processing acoustic space is explored in order to present a sampled set of audio input content to explore the safety of the resulting output electric/acoustic stimulation. In the parameter phase 2 step, the configurable space for realizable electrical stimulation pulses is determined, and overall stimulation reliability and safety are evaluated. The proposed protocol is applied and demonstrated using Costakis Cochlear Implant Mobile. Assessment protocol observations, results, and additional best practices for subsampling of the acoustic and parameter test spaces are discussed. The proposed analysis-evaluation protocol establishes a viable framework for assessing RP operational safety and reliability. Guidelines for adapting the proposed protocol to address variability in RP configuration due to experimental factors such as custom algorithms, stimulation techniques, and/or individualization are also considered.